Contribution of macroporosity to water flux of a soil under different tillage systems - Soracco, Carlos Germán (2012)
In view of the importance of the macroporosity for the water transport properties of soils, its quantitative assessment is a challenging task. Measurements of hydraulic conductivity (K) at different soil water tensions and the quantification of water-conducting macropores (θM) of a soil under different tillage systems could help understand the effects on the soil porous system and related hydraulic properties. The purpose of this study was to assess the effects of Conventional Tillage (CT), Chisel Plow (CP) and No Tillage (NT) on θM and on K; and to quantify the contribution of macroporosity to total water flux in a loam soil. A tension disc infiltrometer was used at two soil water pressure heads (-5 cm, and 0) to infer θM and K, during fallow. Macroporosity was determined based on the flow contribution between 0 and -5 cm water potentials (K0, K5, respectively), according to the Hagen-Poiseuille equation. The K0 values were statistically higher for CT than for NT and CP. The K5 values did not differ statistically among treatments. The mean K values varied between 0.20 and 3.70 cm/h. For CT, θM was significantly greater than for CP and NT, following the same trend as K0. No differences in θM were detected between CP and NT. With CT, the formation of water-conducting macropores with persistence until post-harvest was possible, while under CP preparation, the water-conducting macropores were not persistent. These results support the idea that tillage affects the soil water movement mainly by the resulting water-conducting macropores. Future studies on tillage effects on water movement should focus on macroporosity.